PERMEABILITY DEVELOPMENT IN VESICULATING MAGMAS: IMPLICATIONS FOR FRAGMENTATION - Klug C.; Cashman K.V. (My University, 1996)
Fragmentation, or the "coming apart" of magma during a plinian eruption, remains one of the least understood processes in volcanology, although assumptions about the timing and mechanisms of fragmentation are key parameters in all existing eruption models. Despite evidence to the contrary, most models assume that fragmentation occurs at a critical vesicularity (volume percent vesicles) of 75–83%. We propose instead that the degree to which magma is fragmented is determined by factors controlling bubble coalescence: magma viscosity, temperature, bubble size distribution, bubble shapes, and time. Bubble coalescence in vesiculating magmas creates permeability which serves to connect the dispersed gas phase. When sufficiently developed, permeability allows subsequent exsolved and expanded gas to escape, thus preserving a sufficiently interconnected region of vesicular magma as a pumice clast, rather than fully fragmenting it to ash. For this reason pumice is likely to preserve information about (a) how permeability develops and (b) the critical permeability needed to insure clast preservation. We present measurements and calculations that constrain the conditions (vesicularity, bubble size distribution, time, pressure difference, viscosity) necessary for adequate permeability to develop. We suggest that magma fragments explosively to ash when and where, in a heterogeneously vesiculating magma, these conditions are not met. Both the development of permeability by bubble wall thinning and rupture and the loss of gas through a permeable network of bubbles require time, consistent with the observation that degree of fragmentation (i.e., amount of ash) increases with increasing eruption rate.